2008
DOI: 10.1136/gut.2008.165381
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early gastric cancer: a large-scale feasibility study

Abstract: Precise assessment of curability with successful one-piece resection may reduce tumour recurrence after ESD. The prognosis of EGC patients treated by ESD is likely to be excellent, though further longer follow-up studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
489
9
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(542 citation statements)
references
References 18 publications
31
489
9
13
Order By: Relevance
“…However, the prognosis in patients with SM-GCs treated by ESD remains unspecified, and the actual feasibility of ESD for SM-GCs remains controversial. To our knowledge, although outcomes of EGCs resected by ESD have been reported [10][11][12][13][14][15][16][17], there are no reported comparisons between SM1-GC and SM2-GC. Therefore, we studied outcomes in patients with SM-GCs treated by ESD to determine the feasibility of the procedure across classifications.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the prognosis in patients with SM-GCs treated by ESD remains unspecified, and the actual feasibility of ESD for SM-GCs remains controversial. To our knowledge, although outcomes of EGCs resected by ESD have been reported [10][11][12][13][14][15][16][17], there are no reported comparisons between SM1-GC and SM2-GC. Therefore, we studied outcomes in patients with SM-GCs treated by ESD to determine the feasibility of the procedure across classifications.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, examining the submucosal invasive portion is quite important for predicting lymph node metastasis. In reporting outcomes of ESD for EGCs [10][11][12][13][14][15][16][17], Goto et al [10] noted 5-year overall and disease-specific survival rates of 96.2 and 100%, respectively, with neither lymph node metastasis nor other-organ metastasis. Gotoda et al [11] found no significant difference in overall survival between EGCs that met the guideline criteria and those that met the expanded criteria.…”
Section: Discussionmentioning
confidence: 99%
“…prognosis and less surgical trauma [7][8][9]. The 5-year survival rate in advanced gastric cancer patients is very low, even after surgery-predominant combined treatment, and the survival rate of gastric cancer patients in Western countries is only 20-30 % [10,11].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…1Endoscopic resection, including endoscopic submucosal dissection (ESD), is currently accepted widely as an effective, minimally invasive local treatment for early gastric cancer with a negligible risk of lymph node metastasis, delivering a favorable long-term outcome [1][2][3][4][5][6][7]. However, the development of metachronous gastric cancer (MGC), owing to the preservation of the entire stomach after endoscopic resection, remains a possibility [8][9][10].…”
Section: Introductionmentioning
confidence: 99%